1994
DOI: 10.1103/physrevc.49.2950
|View full text |Cite
|
Sign up to set email alerts
|

Construction of high-qualityNNpotential models

Abstract: We present an updated version (Nijm93) of the Nijmegen soft-core potential, which gives a much better description of the np data than the older version (Nijm78). The χ 2 per datum is 1.87. The configuration-space and momentum-space versions of this potential are exactly equivalent; a unique feature among meson-theoretical potentials. We also present three new NN potential models: a non-local Reid-like Nijmegen potential (Nijm I), a local version (Nijm II), and an updated regularized version (Reid93) of the Rei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
2,113
0
17

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,527 publications
(2,189 citation statements)
references
References 30 publications
59
2,113
0
17
Order By: Relevance
“…We expect that the results from a fully consistent calculation will not deviate significantly from the results we obtain here. The numbers below correspond to the Argonne v 18 potential [45], but results for the Reid93 and Nijmegen II potentials [44] agree within 5%. This is less than the error of order m π /M QCD ∼ 20% intrinsic to χPT in lowest order.…”
Section: Edm Of the Deuteronmentioning
confidence: 92%
See 2 more Smart Citations
“…We expect that the results from a fully consistent calculation will not deviate significantly from the results we obtain here. The numbers below correspond to the Argonne v 18 potential [45], but results for the Reid93 and Nijmegen II potentials [44] agree within 5%. This is less than the error of order m π /M QCD ∼ 20% intrinsic to χPT in lowest order.…”
Section: Edm Of the Deuteronmentioning
confidence: 92%
“…The deuteron EDM has been studied before in the meson-exchange picture [36,37,38,39,40], with various degrees of sophistication in the treatments of the P -and Tconserving interaction H P T . Using modern high-quality phenomenological potentials [44,45], Ref. [39] found that the model dependence of H P T is rather small for a deuteron EDM generated by the OPE sector of the / P/ T interaction.…”
Section: Edm Of the Deuteronmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the construction of V low−k begins with one of a number of available realistic models [21,22,23,24,25] for the nucleon-nucleon (NN) potential V N N . While these models agree well in the low momentum (long range) region, where they are just given by the one pion exchange interaction, in the high momentum (short range) region they are rather uncertain and, in fact, differ significantly from one another.…”
Section: Introductionmentioning
confidence: 99%
“…This family includes the Nijm-I, Nijm-II, and Reid93 potentials [ 3], the Argonne V 18 [ 4], and the CD-Bonn potential [ 5,6]. Later, also the highly non-local potential by Doleschall et al [ 7] and the "CD-Bonn + ∆" model by Deltuva et al [ 8] joined the club.…”
Section: Historical Perspectivementioning
confidence: 99%